Impact of Compensation Management on Employee Job Satisfaction - Khati, Prem Bahadur (Journal of Research in Education, 2025)
The aim of this study is to find out the common compensation management practices and their effect on job satisfaction of employees. The required data were collected by means of a structured questionnaire which was distributed to the employees from ten commercial banks. The methods used for data analysis were Descriptive statistics, Kendall’s Tau correlation, and multiple regression analysis. The study finds the relation between the compensation variables: salary, promotion, bonus, recognition, and job security along with their impact on job satisfaction of employees in commercial banks of Nepal. The result shows that the compensation variables are positively related to job satisfaction of employees, meaning higher the compensation variables higher the job satisfaction. Among these factors, job security was seen as the most influential factor for job satisfaction of employees. The findings suggest that both financial and non-financial compensation elements are important for job satisfaction of Nepalese commercial banks. This study provides practical guidance for bank management and adds empirical evidence to the limited research on compensation management in Nepal’s banking sector, especially in Sudurpaschim Province of Nepal.